It is posible to speak of health from disability (Revista Venezolana de Salud Pública, 2018)
The following essay is a discussion about the possibility of conceptualizing health from disability; to do a review on current notions of health and disability was performed. The concept of health has gone through a continuous process of signification which reached its turning point in 1948, the definition adopted by the World Health Organization. Currently there is no single definition about the aspirations of the standard of living that people aspire to achieve, therefore, any new definition of health must be organic, systemic, dynamic and positive. More than sixty years of the definition of health, the reality is that there are problems related to health conditions such as disability that have been measuring invariably from the biomedical model, in that sense, it seems that it is impossible to understand the disability beyond the eternal disease. Following the adoption in 2001 of the International Classification of Functioning, health and disability, opened new vistas in the field, the redirection of vision disability on expectations placed on the functioning of people and the multidirectional interactions that arise between people and context in which it operates autonomously. To do this, a conceptualization of health, which transcends the realm of the purely corporeal involving factors such representations and socio-environmental relationships are raised
Keywords: health, wellness, illness, disability; health; wellness